Dialysis in Adults in Year 2000 in the Republic of Macedonia - Polenakovic, M.H.; Sikole, A.; Grozdanovski, R.; Amitov, V; Stojkovski, Lj.; Oncevski, A.; Grcevska, L; Dzikova, S.; Cakalaroski, K.; Bogdanovska, S.; Gerasimovska, V.; Gerasimovska B.; et al. (SAGE Publications, 2002)
1,019 adult patients with terminal renal failure were treated with dialysis (D) in the first part of the year 2000 in the Republic of Macedonia. 1,010 patients (99%) were treated with chronic intermittent (maintenance) hemodialysis (HD) while nine patients (1%) were on continuous ambulatory peritoneal dialysis (CAPD). For the children, a special peritoneal dialysis program was developed; 509 patients per million of the population (PMP) were on dialysis. The Republic of Macedonia is, therefore, among those central and eastern European countries with a higher PMP number in the treatment of end-stage renal disease, following Croatia, the Czech Republic and Slovenia. The patients were treated at 18 Centers in a network of HD Centers at a distance of 30–50 km. from their place of residence in order to facilitate their access to treatment and to work. All patients who have had symptoms indicating need for treatment with D were accepted for treatment. The government payed all the expenses of the treatment and the salaries of the staff. 56% were male and 44% were female patients. The youngest patient was aged 9 and the oldest was 82 years old. There has been an increase in the age of the patients on D as well as an increase in their number. In 1993 we had 727 patients being treated with D, and now we have 1,019 with a constant increase in the number of patients with ESRD and a need for D and renal transplantation. Mortality per year at the different Centers ranged from 8–19% in 1999 and the average is 12%. Glomerulonephritis (GN) – both primary and secondary – is the main cause of renal failure (RF) in some Centers up to 45%. Tubulo-interstitial disease follows GN. ADPKD patients constitute 9.4% with a difference among the Centers of 3–29%, and diabetic nephropathy is found in 10%, 5–15% in different Centers. 11–61% of patients have an unknown etiology. 352 patients are on treatment with human recombinant erythropoietin (rhuEPO) – in some Centers up to 60%. The mode of application was subcutaneous and the initial dose is 20 U/kg body weight and the mean maintenance dose of EPO per patient weekly is 4,000 U. The Cimino-Brescia arteriovenous fistula is being applied as a standard vascular access. The survival rate of our patients treated with maintenance HD at 5 years was 58%. CAPD and particularly renal transplantation are to be further developed as alternative methods in treating terminal renal failure.